Investigação espectroscópica dos carbonilos heterobimetálicos cis-[Fe(CO)4(HgX)2], X = Cl, Br,I - Zamian, José Roberto; Mauro, Antonio Eduardo [UNESP]; Nogueira, Vânia Martins [UNESP] (Sociedade Brasileira de Química, 1999)
The series of compounds cis-[Fe(CO)4(HgX)2], X=Cl,Br,I shows an octahedral geometry around the iron atom with the two HgX groups cis to each other. In this paper the assignment for the carbonyl stretching modes and the calculation of their force constants were performed on the basis of the Cotton-Krainhanzel model. Taking into account all the data from the IR, 199Hg NMR and UV-vis spectra it is possible to verify the influence of X on the electronic densities at the metallic centers.
Spectroscopic studies of heterobimetallic carbonyls cis-[Fe(CO)4(HgX)2], X=Cl, Br, I
Keywords: iron carbonyls; mercury; spectroscopic studies